NEEDS FOR LOVE AND BELONGINGNESS IN THE CHARACTER OFGIACOMO CASANOVA IN CASANOVA MOVIE (2005): A HUMANISTIC PSYCHOLOGICAL APPROACH - UTFIATUN, SITI UMI (2011)
The major problem of this study is to reveal how the needs for love and belongingness reflected in Casanova movie directed by Lasse Hallstrom. The objectives of the study are to analyze the movie based on its structural elements and on the humanistic psychology analysis. In analyzing the movie, the researcher uses qualitative study. There are two kinds of data source, namely primary and secondary data source. The primary data is the movie of casanova, while the secondary data is any literature related with this study. The writer collects the data from both primary and secondary data sources by using library research. The technique of data analysis is descriptive technique. The result of the research shows that: First, structural elements of casanova movie build good unity. Second, Casanova movie describes the needs for love and belongingness of Giacomo Casanova as major character. Third, Casanova is a playboy, but he must take a wife and he must be faithful to her.